Gender Differences in Competitiveness - René Böheim; Dominik Grübl; Mario Lackner (ifo DICE Report, 2017)
Women are globally under-represented in top-tier jobs, and according to recent data, in 2013 only around 20 percent of board members in OECD countries were female (OECD, 2013). In addition, empirical studies using different research strategies and rich data consistently find that women earn less than men (e.g. Weichselbaumer and Winter-Ebmer, 2005). Differences in formal qualification levels between men and women have converged over the past decades (Goldin 2006) and cannot explain differences in labour market outcomes between men and women at present as well as in earlier decades. Apart from classical wage discrimination theories (Becker, 1957), part of this gender gap in labour market outcomes could be explained by systematic gender differences in competitiveness. Attitudes towards competitiveness are relevant for educational decisions, during wage negotiations or for occupational choices. For example, women tend to choose different majors in tertiary education (Zafar, 2013) and choose different occupations than men (Goldin, 2014). Differences in competitiveness might determine a career path if promotions are linked to performance in competitive settings. Reuben, Sapienza, and Zingales (2015) ascertain that male graduates are more competitive than female graduates in the beginning of their career and they are more likely to select themselves into higher paid industries. Overall, they conclude that gender differences in competitiveness explain about 10 percent of the gender gap in earnings.
Keywords: J16; 330; Lohnstruktur; Erwerbsverlauf; Führungskräfteauswahl; Wettbewerb; Geschlechterdiskriminierung; Weibliche Führungskräfte; Arbeitsangebot